Insulin receptor substrate 1 overexpression promotes survival of glioblastoma cells through AKT1 activation - Gorgisen, Gokhan; Yaren, Zafer (Folia Neuropathologica, 2020)
Glioblastoma multiforme (GBM) is the most common and malignant type of central nervous system tumours in adults. Strict regulation of glucose homeostasis has a significant role in GBM pathogenesis. Insulin receptor substrate 1 (IRS1) protein is the most important adaptor molecule involved in the regulation of glucose metabolism. It interacts with many cancer-related receptors and its overexpression is strongly associated with cell proliferation and survival. Our study was aimed to understand the role of IRS1 proteins in GBM cell viability. U-87 MG cells were transfected with pcDNA3.1-flagtagged-human IRS1 expression vector. Insulin induced phosphorylation levels of IRS1, AKT1 and ERK1/2 and Grb2 expression were examined to determine the effects of ectopic IRS1 overexpression on insulin signalling and the viability levels of U-87 MG cells were determined by MTT analysis. Overexpression of IRS1 in U-87 MG cells led to an increase in cell viability. Its overexpression also increased Grb2 expression and phosphorylation of AKT1 through elevation of IRS1 tyrosine phosphorylation in IRS1-transfected U-87 MG cells compared to control and mock transfected groups. Our study showed that increased IRS1 expression and activation may promote the cell viability via AKT1 activation. IRS1 signalling may be considered as a therapeutic target for further studies.